DESIGNING SALAM-MUZARA’AH LINKED WAQF TO FINANCING AGRICULTURAL SECTOR - Rifaldi Majid (Journal of Islamic Monetary Economics and Finance, 2021)
The main objective of this study is to propose an innovative integrated financing model at the microfinance level for the agricultural sector and how to mitigate the risk associated with the model. In the study, we perform in-depth interviews of experts and gather secondary data from relevant sources. The proposed model is called Salam-Muzara’ah Linked Waqf (SMW) as a sharia-compliant scheme that integrates Islamic commercial finance through the salam and muzara’ah contract with Islamic social finance through the utilization of cash waqf return as well as using the idle waqf land as agricultural lands to be implemented by Baitul Maal wat Tamwil (BMT). In the model, the risk of commodities delivered by farmers to BMT is subsidized or borrowed by Nazhir of waqf land while the surplus of cash waqf is distributed to cover Murabaha margin of necessary agricultural equipment purchased from BMT. This research is expected to solve the problem of limited land and financing as well as to create innovation and inclusiveness of Islamic financial products through the synergy of all parties in the agricultural sector.